2023
DOI: 10.1002/jat.4510
|View full text |Cite
|
Sign up to set email alerts
|

The reproductive and transgenerational toxicity of microplastics and nanoplastics: A threat to mammalian fertility in both sexes

Abstract: Microplastics (MPs) and nanoplastics (NPs) are extensively distributed in the environment. However, a comprehensive review and in‐depth discussion on the effects of MPs and NPs to reproductive capacity and transgenerational toxicity on mammals, especially on humans, is lacked. It is suggested that microplastics and nanoplastics could accumulate in mammalian reproductive organs and exert toxic effects on the reproductive system for both sexes. For males, the damage of microplastics consists of abnormal testicul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 104 publications
0
1
0
Order By: Relevance
“…The existing literature suggests a potential decline in fertility associated with environmental exposure to microparticles and nanoparticles derived from these polymers. They may accumulate in mammalian reproductive organs, exerting toxic effects on the reproductive systems of both genders, potentially leading to transgenerational impacts ( Afreen et al , 2023 ; He and Yin, 2024 ). However, there is a noticeable gap in research concerning the direct toxicity of these polymers on gametes and embryos.…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature suggests a potential decline in fertility associated with environmental exposure to microparticles and nanoparticles derived from these polymers. They may accumulate in mammalian reproductive organs, exerting toxic effects on the reproductive systems of both genders, potentially leading to transgenerational impacts ( Afreen et al , 2023 ; He and Yin, 2024 ). However, there is a noticeable gap in research concerning the direct toxicity of these polymers on gametes and embryos.…”
Section: Discussionmentioning
confidence: 99%
“…This damage results from oxidative stress, inflammation, cell death in the testes, abnormal cell processes, and hormonal axis disruption. In females, MNPs cause abnormalities in ovarian and uterine structure, disrupt hormonal balance, induce cell death in granulosa cells, disrupt the hypothalamic-pituitary-ovary axis, and lead to tissue fibrosis [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The adverse effects of EDCs include oxidative stress-induced tissue damage leading to apoptosis, developmental abnormalities, impaired gamete quality, metabolic disorders, neurotoxicity, and epigenetic changes due to in-utero exposure ( 185 189 , 253 ). Research has indicated that exposure to MPs can lead to abnormalities in the structure of testicular and sperm cells, reduced sperm viability, and disruption of the endocrine system in male individuals ( 190 ). The harm inflicted by MPs on the male reproductive system may result in reproductive dysfunction and reduced fertility ( 191 ).…”
Section: Microplastics In Different Environmentsmentioning
confidence: 99%